Eﬀect of starvation and crowding on some physiological parameters of young common carp (Cyprinus carpio L. ) - Shaima Saleh Mahmood (Journal of Kerbala for Agricultural Sciences, 2024)
Fish frequently undergo stress during aquaculture or experimental operations, which can change any physiological parameter and have an impact on the success of rearing the fish or the outcomes of the research.The purpose of this study was to investigate how different stressors affected some physiological parameters of common carp (Cyprinus carpio L.). A total of 162 common carp with body weights ranging from 60.4 to 62.8 g which were evenly distributed in plastic aquaria were subjected to three stressor factors: crowding, starvation, and a combination of starvation and crowding for durations of 24, 72, and 144 hours. Cortisol levels were 167.55, 183.8, 212.8 nmol/L, and 222.65 nmol/L, respectively, for control, crowding, starvation and (crowding+starvation). Unlike haematocrit, which was consistently lower in starved fish, hemoglobin content did not appear to be influenced by starvation. Stressors such as starvation, crowding, and their combination had a substantial influence on typical automotive physiological measures such as cortisol level, blood glucose and hematocrit.